High-throughput profiling reveals perturbation of endoplasmic reticulum stress-related genes in atherosclerosis induced by high-cholesterol diet and the protective role of vitamin E - KARTAL ÖZER, NESRİN (WILEY, 2020)
Formation of atherosclerotic plaques, called atherogenesis, is a complex process affected by genetic and environmental factors. It was proposed that endoplasmic reticulum (ER) stress is an important factor in the pathogenesis of atherosclerosis and that vitamin E affects atherosclerotic plaque formation via its antioxidant properties. Here, we investigated ER stress-related molecular mechanisms in high-cholesterol diet (HCD, 2%)-induced atherosclerosis model and the role of vitamin E supplementation in it, beyond its antioxidant properties. The consequences of HCD and vitamin E supplementation were examined by determining protein levels of ER stress markers in aortic tissues. As vitamin E supplementation acts on several unfolded protein response (UPR) factors, it decreased ER stress induced by HCD. To elucidate the associated pathways, gene expression profiling was performed, revealing differentially expressed genes enriched in ER stress-related pathways such as the proteasome and the apoptosis pathways. We further assessed the proteasomal activity impaired by HCD in the aorta and showed that vitamin E reversed it to that of control animals. Overall, the study characterized the effects of HCD and vitamin E on ER stress-related gene expression, revealing the role of proteolytic systems during atherogenesis.
Keywords: atherosclerosis; ER stress; high-cholesterol diet; RNA-sequencing; vitamin E; SCAVENGER RECEPTOR EXPRESSION; UNFOLDED PROTEIN RESPONSE; PROTEASOME; CELLS; MECHANISMS; APOPTOSIS